Development of a Model to Predict Vibrations Induced by Blasting Excavation of Deep Rock Masses under High In Situ Stress - Yong Fan; Xianze Cui; Zhendong Leng; Yurong Zhou; Junwei Zheng; Feng Wang (Shock and Vibration)
During the process of blasting excavation of deep rock masses under high in situ stress, energy produced by the explosive and the strain energy released by rock mass excavation constitute the energy source of vibration. However, in traditional Sadov’s empirical formula, the energy produced by explosive explosion is only considered which makes the error higher when it is used to predict the blasting-induced vibration peak under the condition of high in situ stress. In this study, energy transformation and distribution mechanisms caused by excavation of deep rock masses were analyzed at first. Then, a prediction model of vibration peak based on the principle of energy balance was established by dimension analysis. Finally, the proposed model was trained and tested with the vibration data monitored during the blasting excavation of deep buried tunnel in Jinping II hydropower station. The result shows that compared with the traditional prediction model, the proposed model has higher fitting correlation coefficient and lower root-mean-square error, which can be better applied to the prediction of vibration induced by blasting excavation of deep rock masses under high in situ stress.